Coupled impacts of soil acidification and climate change on future crop suitability in Ethiopia - Jimma, Tamirat B.; Chemura, Abel; Spillane, Charles; Teferi, Demissie; Abera, Wuletawu; Ture, Kassahun; Terefe, Tadesse; Solomon, Dawit; Gleixner, Stephanie (MDPI, 2024)
Agricultural sustainability faces challenges in the changing climate, particularly for rain-fed systems like those in Ethiopia. This study examines the combined impacts of climate change and soil acidity on future crop potential, focusing on Ethiopia as a case study. The EcoCrop crop suitability model was parameterized and run for four key food crops in Ethiopia (teff, maize, barley and common wheat), under current and mid-century climate conditions. To assess the impacts of soil acidification on crop suitability, a simulation study was conducted by lowering the soil pH values by 0.5, 1.0 and 1.5 and re-running the suitability model, comparing the changes in the area suitable for each crop. Our evaluation of the model, by comparing the modeled suitable areas with reference data, indicated that there was a good fit for all the four crops. Using default soil pH values, we project that there will be no significant changes in the suitability of maize, barley and wheat and an increase in the suitability of teff by the mid-century, as influenced by projected increases in rainfall in the country. Our results demonstrate a direct relationship between the lowering of soil pH and increasing losses in the area suitable for all crops, but especially for teff, barley and wheat. We conclude that soil acidification can have a strong impact on crop suitability in Ethiopia under climate change, and precautionary measures to avoid soil acidification should be a key element in the design of climate change adaptation strategies.